PERAN ACCOUNT RECEIVABLE SECTION DI JAMBULUWUK MALIOBORO BOUTIQUE HOTEL YOGYAKARTA - , KURNIA MEGA KARTINI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Increasing competition in the business in Indonesia, so many companies moving company to grow as the tourism sector. Increase the number of people willing to do a tour, make companies trying to build supporting infrastructure by offering a wide variety of products and services. One of company that is engaged in the development of accommodation services business, is PT ARCS HOUSE. The company is focused in the areas of accommodation, including hotels and resorts. The purpose of this final study is to determine the role of an Accounts Receivable Section of the handling of invoices in Jambuluwuk Malioboro Boutique Hotel. Data analysis techniques used include descriptive qualitative data analysis techniques. Qualitative descriptive data analysis techniques are used to provide an overview of the actual variable. From the analysis it can be seen the role and work procedures Accounts Receivable Section from the beginning to the end. Accounts Receivable section is a sub section of the Finance & Accounting Department which plays an important role over income support and smoothness of the company's cash flow. Accounts Receivable section are fully responsible for any form of company accounts in order to maintain the most up to support the needs of both companies will be capital for the company's operations.